2014
DOI: 10.1007/s10811-014-0441-0
|View full text |Cite
|
Sign up to set email alerts
|

Purification, primary structure, and biological activity of the high-mannose N-glycan-specific lectin from cultivated Eucheuma denticulatum

Abstract: Three isolectins from cultivated Eucheuma denticulatum were isolated. They were commonly monomeric proteins of about 28 kDa with a range of averaged molecular weights from 27,834 to 27,868 Da among the isolectins and shared almost the same 20 N-terminal amino acid sequences. Complementary DNA (cDNA) cloning based on the rapid amplification cDNA ends (RACE) methods elucidated the full-length sequence of EDA-2 which encodes 269 amino acids, including initiating methionine, with four tandemly repeated domains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 46 publications
(57 reference statements)
4
22
0
3
Order By: Relevance
“…In the present study, we have determined the primary structure of KSA-2, and confirmed that it strongly resembles those of lower organisms, such as OAA from O. agardhii Sato and Hori, 2009), ESA-2 from E. serra , EDA-2 from E. denticulatum (Hung et al, 2015), MBHA from M. xanthus (Romeo et al, 1986;Koharudin et al, 2012), BOA from B. oklahomensis (Whitley et al, 2013) and PFL from P. fluorescens Pf0-1 (Sato et al, 2012) (Fig. 4), including its molecular size and the presence of tandemly repeated motifs.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In the present study, we have determined the primary structure of KSA-2, and confirmed that it strongly resembles those of lower organisms, such as OAA from O. agardhii Sato and Hori, 2009), ESA-2 from E. serra , EDA-2 from E. denticulatum (Hung et al, 2015), MBHA from M. xanthus (Romeo et al, 1986;Koharudin et al, 2012), BOA from B. oklahomensis (Whitley et al, 2013) and PFL from P. fluorescens Pf0-1 (Sato et al, 2012) (Fig. 4), including its molecular size and the presence of tandemly repeated motifs.…”
Section: Discussionsupporting
confidence: 78%
“…The species-specific antibacterial activities have been reported for the lectins from the red algae, E. serra and Galaxaura marginata, in which both lectins displayed antibacterial activity toward the fish pathogen Vibrio vulnificus,but not toward Vibrio neresis and Vibrio pelagius (Liao et al, 2003), and lectins from E. denticulatum toward the shimp pathogen V. alginolyticus, but not toward V. parahaemolyticus and V. harveyi (Hung et al, 2015). Although antibacterial activities have been reported for lectins from various biological sources (Santi-Gadelha et al, 2006;Charungchitrak et al, 2011;Riera et al, 2003), there seems to be little reported for the growth-inhibiting activity against shrimp and fish pathogens, except the high-mannose N-glycan specific lectins from carrageenophytes mentioned above.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The recognition mode of KAAs is absolutely different from the other high-mannose specific antiviral lectins including CV-N, GRFT, SVN, MVL, and AH . We also reported the same oligosaccharide binding properties in ESA-2 ) and OAA , and recently in KSA from K. striatum (Hung et al 2011) and EDA from E. denticulatum (Hung et al 2015). A lectin PFL from Pseudomonas fluorescens Pf0-1 belonging to this lectin family also tends to preferentially recognize highmannose glycans with α1-3 Man exposed in the D2 arm but not to other sugar types including complex N-glycans and Oglycans, as revealed by screening with a glycan array having 611 glycan targets (Sato et al 2012).…”
Section: Discussionsupporting
confidence: 78%
“…A lectin ESA-2 from a red alga Eucheuma serra (Kawakubo et al 1997) was recently found to possess the unique binding specificity with the preferential affinity for high-mannose N-glycans bearing the nonreducing terminal α1-3 Man in D2 arm ). Since then, several lectins with similar binding specificity were isolated from some lower organisms, including red algae (Kawakubo et al 1999;Sato et al 2011a;Hung et al 2011Hung et al , 2015, a cyanobacterium (Sato et al 2000, and bacteria (Cumsky and Zusman 1979;Sato et al 2012;Koharudin et al 2012;Whitley et al 2013). Interestingly, these lectins commonly had tandem-repeated structures of a similar domain composed of about 67 amino acids, and grouped into two types of four and two repeats Sato et al 2007;Sato and Hori 2009) as exemplified with ESA-2 (four repeats) and a lectin OAA (two repeats) from a freshwater cyanobacterium Oscillatoria agardhii.…”
Section: Introductionmentioning
confidence: 99%